Preference alignment or executive predominance: The rise of states' rulemaking provisions in the U.S. - Brian Baugus; Feler Bose; Jeffry Jacob (Journal of Government and Economics (JGE), 2024)
Before 1941, U.S. regulatory bodies were unrestricted. By 1946, several states and the federal government had imposed restrictions. It further took 40 years for every state to enact an Administrative Procedures Act (APA), a law that dictates how regulatory agencies promulgate regulations. Despite being overlooked, APAs significantly impact states in often missed or ignored ways. We analyzed each state's rulemaking procedures at four different points in time to see if they've increased or decreased restrictions on regulatory agencies. We created two indexes: a Restrictiveness index, a summative index, and another derived from multiple correspondence analysis. We studied how legislative professionalism, interest group constraint, citizen ideology, and government partisanism affect APA restrictions.
Keywords: H70; H73; H79; L51; 330; Administrative procedures act; Delegation; Executive Predominance; Index of Ease of Agency burden; Preference alignment theory; Restrictiveness index